PENURUNAN BEBAN PENCEMAR LIMBAH CAIR RUMAH SAKIT MENGGUNAKAN RANCANG MOVING BED BIOFILTER REACTOR (MBBR) SEBAGAI ALTERNATIF PENGOLAHAN LIMBAH MEDIS DI PROVINSI BANTEN - Masyruroh, Anis; Ramadhan, Agung (Jurnal Kebijakan Pembangunan Daerah, 2024)
Hospitals are health care facilities that produce liquid, solid and B3 waste. The high pollutant load of hospital wastewater in Indonesia causes problems for the environment and other living things. Appropriate technology requires high costs (high cost) in manufacture and maintenance, this is one of the factors that hospitals are reluctant to make WWTP according to standards. This study aims to design a simple WWTP using a Moving Bed Biofilm Reactor (MBBR) and determine the reduction efficiency of hospital wastewater. The number of samples used in this study were 3 samples. WWTP tubs are made of PVC pipes with a total of 5 tanks, namely oil/fat separator tanks, equalization tanks, anoxic tanks, aeration tanks and sedimentation tanks. The efficiency of reducing the quality of hospital wastewater using MBBR is at an average concentration of pH of 9%, TSS of 43%, COD of 31%, BOD5 of 29% and Ammonia of 25%. The results of the influent and effluent differences test in hospital wastewater using SPSS software showed that only the concentrations of COD, BOD5 and Ammonia were significantly different, while there were no significant differences in the concentrations of pH and TSS. From the results of research from three government hospitals and private hospitals in Banten Province, it shows that the liquid waste processing system using MBBR can be successful in reducing waste characteristics.